Association of socioeconomic conditions and quality of life with depression among Laos migrant workers in Northeast Thailand: multilevel-level logistics regression analysis: 10.55131/jphd/2024/220112 - Kongsrima, Supat; Laohasiriwong, Wongsa; Prasit, Nakarin; Sresutham, Puwanart; Nidthumsakul, Nattaporn (Journal of Public Health and Development, 2024)
Currently, an increasing number of workers are migrating to Thailand; a trend that is increasing along with the economic growth of the country. However, the cultural conditions, traditions and adjustments of migrant workers in Thailand have a significant impact on their mental state, leading to mental health problems. This study used a cross-sectional analytical study design and secondary data. This study investigated the relationship of socioeconomic conditions and quality of life with depression among migrant workers from Laos employed in Northeast Thailand. The study was conducted from January 2019 to December 2020. Study participants included 1,205 Laos migrant workers working in Northeast Thailand. Data was analysed using Multi-level Logistic Regression Analysis to determine the relationship of socioeconomic conditions and quality of life with depression. The effects of covariates were controlled and adjusted odds ratio (AOR) values and 95% confidence intervals (CI) are presented. The results of the study revealed that the prevalence of depression was 9.29% (95%CI: 7.78–11.07) and factors affecting depression among Laos migrant workers included low-moderate psychological quality of life (AOR =6.69, CI: 2.96–15.10), low-moderate social quality of life (AOR =4.00, 95%CI: 2.32–6.99) and sufficient income but no savings (AOR=2.56, 95%CI: 1.57–4.19). Therefore, agencies related to migrant workers should focus on developing policies that promote their quality of life, as it directly affects their mental health. This should include the development of social and psychological quality of life as well as income and well-being security, which serves as the foundation for workers who contribute to the country’s sustainable economic and industrial development.